Do bankruptcy profiles of Islamic banks differ across organizational structure? evidence from Malaysia - Nik Nurul Hidayah Nik Zainudin; S. Shahida; Ahmad Azam Sulaiman@Mohamad (Universitas Islam Indonesia, 2019)
Malaysian Islamic banks operate in different organizational structures, namely domestic, locally foreign incorporated, and development financial institutions which may have an influence on their stability. This research evaluates the bankruptcy profiles of 19 selected Malaysian Islamic banks from 2010 to 2017 and analyses the insolvency risk associated with the three different organizational structures. Using the Altman’s Z-Score Model (2000), a stability test was conducted. Findings/Originality: the paper finds that, on average, the development financial institutions were the most stable banks, followed by foreign Islamic banks. It also finds that bigger domestic Islamic banks were situated in the safe zone as they had high Z-score values. Furthermore, asset quality ratio contributed to higher Z-score values. An appropriate asset-liability management therefore helps ensure the stability of Islamic banks in Malaysia. An effective macroprudential supervisory regime must also be in place to increase the resilience of the financial system.